Differences in Inflammation and Bone Resorption between Apical Granulomas, Radicular Cysts, and Dentigerous Cysts - Weber, Manuel; Ries, Jutta; Büttner-Herold, Maike; Geppert, Carol-Immanuel; Kesting, Marco Rainer; Wehrhan, Falk (Journal of Endodontics, 2019)
Introduction: Dental cysts can be of inflammatory (radicular cysts) or noninflammatory (dentigerous cysts) origin. Apical periodontitis is a necrosis of the pulp and infection of the root canal causing the development of apical granulomas or radicular cysts. The immunology of granuloma and cyst formation is important because modern root filling materials are immunologically active and can contribute to the resolution of apical granulomas. In contrast, radicular cysts often require apicectomy. A better understanding of the pathophysiology of inflammation and bone resorption in apical periodontitis could be the basis for developing new root filling materials with superior immunomodulatory properties. Methods: Forty-one apical granulomas, 23 radicular cysts, and 23 dentigerous cysts were analyzed in this study. A tissue microarray of the 87 consecutive specimens was created, and human leukocyte antigen–DR isotype (HLA-DR)-, CD83-, receptor activator of nuclear factor kappa B ligand–, macrophage colony-stimulating factor (MCSF)-, galectin-3 (Gal3)-, CD4-, and CD8-positive cells were detected by immunohistochemistry. Tissue microarrays were digitized, and the expression of markers was quantitatively assessed. Results: HLA-DR, CD83, MCSF, and Gal3 expression was significantly (P < .05) higher in radicular cysts compared with apical granulomas. HLA-DR, CD83, MCSF, receptor activator of nuclear factor kappa B ligand, and Gal3 expression in dentigerous cysts was significantly (P < .05) lower than in both periapical lesions (apical granulomas and radicular cysts). CD4 and CD8 infiltration was not statistically different between apical granulomas and radicular cysts. Dentigerous cysts showed a significantly (P < .05) lower T-cell infiltration than apical periodontitis. The CD4/CD8 ratio was not significantly different between the analyzed groups. Conclusions: The development of radicular cysts in apical periodontitis is associated with an increased expression of myeloid inflammatory markers and bone resorption parameters. Antigen-presenting cells and myeloid cells might be more relevant for the pathogenesis of apical periodontitis than T cells. Increased inflammation might promote the formation of radicular cysts and more pronounced bone resorption.
CRIS-Team Scopus Importer:2019-09-27
Keywords: Apical granuloma; apical periodontitis; bone resorption; follicular cyst; periapical lesion; radicular cysts